Apakah Perilaku Belajar Dan Kecerdasan Spiritual Berpengaruh Terhadap Stres Belajar Mahasiswa Akuntansi? - Moch. Rachmandany Firmansyah; Mahjudin Mahjudin; Dody Suhermawan; Achmad Daengs GS; Enny Istanti (Journal of Management and Creative Business, 2023)
The causes of stress in students can come from their academic life, especially from external demands and their own expectations. External demands can be in the form of coursework, course load, parents' demands to be successful in their studies, and social adjustments in the campus environment. Spiritual intelligence is able to encourage students to achieve success in their studies because spiritual intelligence is the foundation that encourages the effective functioning of intellectual intelligence and emotional intelligence. Study behavior (which consists of the habit of attending lessons, the habit of reading books, the habit of visiting the library, and the habit of taking exams) of a student greatly influences the continuity of his studies. This research is quantitative research in the form of a case study using multiple linear regression analysis methods. The results of data testing show that learning behavior can have a negative but not significant effect on college stress. The results of testing spiritual intelligence show that spiritual intelligence can have a negative but not significant effect on college stress.